(untitled) (Global Journal of Management and Business Research, 2020)
The research paper is aiming at identifying the dark side of Bali and the reason behind the growth of its sex tourism industry in this digital era. The main focus of this research paper is the process by which the digitalization supports stimulating sex tourism in Bali. The researcher is focusing on executing the secondary form of research method to collect necessary data. The data gathering process is carried out with the help of news articles and journals of the previous researches. With the help of the collected information, the researcher can ful fill the research questions with the help of representing the facts in the results and analysis section.